Auxin-induced AUXIN RESPONSE FACTOR4 activates APETALA1 and FRUITFULL to promote flowering in woodland strawberry. (1st May 2021) - Dong, Xiangxiang; Li, Yanjun; Guan, Yuhan; Wang, Shaoxi; Luo, He; Li, Xiaoming; Li, He; Zhang, Zhihong
Abstract: Flowering time is known to be regulated by numerous pathways, such as the autonomous, gibberellin, aging, photoperiod-mediated, and vernalization pathways. These regulatory mechanisms involve both environmental triggers and endogenous hormonal cues. Additional flowering control mechanisms mediated by other phytohormones, such as auxin, are less well understood. We found that in cultivated strawberry ( Fragaria  ×  ananassa ), the expression of auxin response factor4 ( FaARF4 ) was higher in the flowering stage than in the vegetative stage. Overexpression of FaARF4 in Arabidopsis thaliana and woodland strawberry ( Fragaria vesca ) resulted in transgenic plants flowering earlier than control plants. In addition, FveARF4 -silenced strawberry plants showed delayed flowering compared to control plants, indicating that FaARF4 and FveARF4 function similarly in regulating flowering. Further studies showed that ARF4 can bind to the promoters of the floral meristem identity genes APETALA1 ( AP1 ) and FRUITFULL ( FUL ), inducing their expression and, consequently, flowering in woodland strawberry. Our studies reveal an auxin-mediated flowering pathway in strawberry involving the induction of ARF4 expression.